2007
DOI: 10.1002/ejic.200601130
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterisation of Polymer‐Anchored Oxidovanadium(IV) Complexes and Their Use for the Oxidation of Styrene and Cumene

Abstract: The Schiff bases H 2 fsal-ea (I), H 2 fsal-pa (II) and H 2 fsal-amp (III), derived from 3-formylsalicylic acid and 2-aminoethanol, 3-aminopropanol and 2-amino-2-methylpropanol, respectively, have been connected, by means of covalent bonds, to chloromethylated polystyrene cross-linked with 5 % divinylbenzene. On treatment with [VO(acac) 2 ] in dimethylformamide (DMF), these polymer-anchored ligands PS-H 2 fsal-ea (IV), PS-H 2 fsal-pa (V) and PS-H 2 fsal-amp (VI) gave the ox- 6), respectively. The corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…For example, Thiel and coworkers [9] reported that the mesoporous MCM-41 material modified with an oxodiperoxo molybdenum complex was highly efficient and stable for the epoxidation of ciscyclooctene with TBHP. Maurya et al [10] immobilized oxovanadium(IV) or dioxovanadium(V) complexes onto polystyrene and found that these supported catalysts were highly active and recyclable for styrene epoxidation.…”
Section: Introductionmentioning
confidence: 98%
“…For example, Thiel and coworkers [9] reported that the mesoporous MCM-41 material modified with an oxodiperoxo molybdenum complex was highly efficient and stable for the epoxidation of ciscyclooctene with TBHP. Maurya et al [10] immobilized oxovanadium(IV) or dioxovanadium(V) complexes onto polystyrene and found that these supported catalysts were highly active and recyclable for styrene epoxidation.…”
Section: Introductionmentioning
confidence: 98%
“…[5][6][7] Many vanadium complexes provide a suitable structural and/or functional model for these enzymes. [8][9][10] Oxidations of aliphatic as well as aromatic substrates [11][12][13][14] including organic sulfides to sulfoxides, 15,16 catalysed by vanadium complexes, have also been achieved in excellent yield. Recently, we have directed our investigations into the coordination chemistry of vanadium in its higher oxidation states.…”
Section: Introductionmentioning
confidence: 99%
“…The good performance of these catalysts is possibly due to the facile formation of peroxide species in the presence of H 2 O 2 as well as the ease in transferring oxygen from the intermediate peroxide species to the substrate. However, the complexes slowly convert back to the oxidovanadium(V) species [35].…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…Scheme 1 shows that the oxovanadium(IV) complex (a) is oxidized to oxovanadium(V) (b) by H 2 O 2 and further Intermediate [X] is stabilized by the formation of a hydrogen bond between phenol and the oxygen atom of the active oxidant. Finally in the rate-determining step, the products are obtained and the catalyst is regenerated [35] with a firstorder rate constant k 1 . In this process, the intermolecular redox reaction between phenol and H 2 O 2 is transformed into an intramolecular electron transfer reaction in the intermediate [X], leading to a large decrease in the activation energy and concomitant enhancement in the rate.…”
Section: Reaction Mechanismmentioning
confidence: 99%